2011
DOI: 10.3758/s13414-011-0179-6
|View full text |Cite
|
Sign up to set email alerts
|

Response specific temporal expectancy: Evidence from a variable foreperiod paradigm

Abstract: When a stimulus-response event is frequently paired with a specific foreperiod, response performance for this event is improved after this foreperiod. This phenomenon is referred to as specific temporal expectancy.In four experiments, we investigated whether stimulus-or response-related processing benefits from specific temporal expectancy. In a speeded choice reaction task, different features of the imperative stimuli were frequently paired with foreperiods in such a way that only in some experiments were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 78 publications
(72 reference statements)
5
35
0
Order By: Relevance
“…Apart from stimulus identity, expectations can also involve the specific timing of stimuli (e.g., Coull and Nobre, 2008;Fischer et al, 2013;Grosjean et al, 2001;Klein-Flügge et al, 2011;Nobre et al, 2007;Niemi and Näätänen, 1981;Schwartze and Kotz, 2013) and specific response elements (e.g., Thomaschke et al, 2011). Expectation effects occur in many experimental designs -irrespective of whether one is focusing on them in the research question or tries to control and balance them as the focus lies elsewhere.…”
Section: The Distinction Between Self-generated and Cue-induced Expecmentioning
confidence: 98%
“…Apart from stimulus identity, expectations can also involve the specific timing of stimuli (e.g., Coull and Nobre, 2008;Fischer et al, 2013;Grosjean et al, 2001;Klein-Flügge et al, 2011;Nobre et al, 2007;Niemi and Näätänen, 1981;Schwartze and Kotz, 2013) and specific response elements (e.g., Thomaschke et al, 2011). Expectation effects occur in many experimental designs -irrespective of whether one is focusing on them in the research question or tries to control and balance them as the focus lies elsewhere.…”
Section: The Distinction Between Self-generated and Cue-induced Expecmentioning
confidence: 98%
“…For instance, in the time-event correlation paradigm, each specific S2-response pair has an equal probability of occurrence on each trial, but one pair is more probable after a short FP than after a long FP (e.g., 4/5 vs. 1/5), whereas these probabilities are reversed for another pair. It has been shown that the ensuing time-event correlation gets gradually expressed in behavior: Over the course of the experimental session, participants come to respond faster and more accurately to S2 when it occurs after its typical FP than when it occurs after its atypical FP (e.g., Miller and Schröter, 2002, Experiment 8; Wagener and Hoffmann, 2010; Thomaschke et al, 2011; Thomaschke and Dreisbach, 2013, in press). Meanwhile, participants remain generally unaware of this time-event correlation, as evidenced by self-report after the experimental session (e.g., Thomaschke et al, 2011; Thomaschke and Dreisbach, in press).…”
Section: Accounting For the Family Of Fp Effectsmentioning
confidence: 99%
“…Performance would be impaired if, because of a malfunction of the machine, the coffee nozzle spouted after the time the machine typically took to display an error message (i.e., 10 s) or if the error message appeared at the time when the coffee was expected to be dispensed (i.e., 2-3 s; see Thomaschke, Wagener, Kiesel, & Hoffmann, 2011a;Wagener & Hoffmann, 2010). The expectancy described in this example has been termed specific temporal expectancy (Thomaschke, Kiesel, & Hoffmann, 2011). Specific temporal expectancy can be defined as expectancy for a combination of an event and a point in time.…”
Section: Research Reportmentioning
confidence: 99%